Berberine Protects C17.2 Neural Stem Cells From Oxidative Damage Followed by Inducing Neuronal Differentiation - Shou, Jia-Wen; Cheung, Chun-Kai; Gao, Jian; Shi, Wei-Wei; Shaw, Pang-Chui (Frontiers in Cellular Neuroscience, 2019)
Neurodegeneration is the loss of structure and/or function of neurons. Oxidative stress has been suggested as one of the common etiology in most of the neurodegenerative diseases. Previous studies have demonstrated the beneficial effects of berberine in various neurodegenerative and neuropsychiatric disorders. In this study, we hypothesized that berberine could protect C17.2 neural stem cells from 2,2'-Azobis(2-amidinopropane) dihydrochloride (AAPH)-induced oxidative damage then promote neuronal differentiation. AAPH was used to induce oxidative damage. After the damage, berberine protected C17.2 cells were kept cultured for another week in differentiation medium with/without berberine. Changes in cell morphology were detected by microscopy and cell viability was determined by MTT assay. Real-time PCR and western blot analysis were performed to confirm the associated pathways. Berberine was able to protect C17.2 neural stem cells from the oxidative damage. It lowered the cellular reactive oxygen species (ROS) level in C17.2 cells via Nuclear Factor Erythroid 2-Related Factor 1/2 (NRF1/2) - NAD(P)H Quinone Dehydrogenase 1 (NQO-1) - Heme Oxygenase 1 (HO-1) pathway. It also down-regulated the apoptotic factors- Caspase 3 and Bcl2 Associated X (Bax) and upregulated the anti-apoptotic factor- Bcl2 to reduce cell apoptosis. Besides, berberine increased C17.2 cell viability via up-regulating Extracellular-signal-Related Kinase (ERK) and phosphor-Extracellular-signal-Related Kinase (pERK) expression. Then, berberine promoted C17.2 cell to differentiate into neurons and the differentiation mechanism involved the activation of WNT/-catenin pathway as well as the upregulation of expression levels of pro-neural factors Achaete-Scute Complex-Like 1 (ASCL1), Neurogenin 1 (NeuroG1), Neuronal Differentiation 2 (NeuroD2) and Doublecortin (DCX). In conclusion, berberine protected C17.2 neural stem cells from oxidative damage then induced them to differentiate into neurons.